2022
DOI: 10.1002/jrs.6332
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced heating of porous Ge layers implanted with Ag+ and Cu+ ions

Abstract: Porous Ge layers consisting of nanowires were formed by low-energy highdose implantation of monocrystalline c-Ge substrate with Ag + and Cu + ions. The obtained layers were studied by Raman spectroscopy using solid-state and He-Ne exciting lasers with wavelength of 532 and 633 nm, respectively. The crystalline volume fraction and local temperature of porous layers at the surface sites of laser probing were determined. To interpret the change in the shape of the spectra under the action of laser radiation, deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Samples 3 and 4 demonstrated a smaller percentage of the crystalline phase at the least intense excitation. Thus, the assumption expressed in Pavlikov et al [ 7 ] and Sharafutdinova et al [ 8 ] is experimentally confirmed that if the penetration depth of radiation is less than the thickness of the porous layer, then its local heating occurs to temperatures sufficient for recrystallization. This is facilitated by the low thermal conductivity of the PGe layer.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Samples 3 and 4 demonstrated a smaller percentage of the crystalline phase at the least intense excitation. Thus, the assumption expressed in Pavlikov et al [ 7 ] and Sharafutdinova et al [ 8 ] is experimentally confirmed that if the penetration depth of radiation is less than the thickness of the porous layer, then its local heating occurs to temperatures sufficient for recrystallization. This is facilitated by the low thermal conductivity of the PGe layer.…”
Section: Resultsmentioning
confidence: 84%
“…The intensity of the exciting laser radiation ( I) was increased from a minimum value of 30 to 3000 W/cm 2 . It was demonstrated earlier [ 7,8 ] that initial and final spectra measured at the same spot on the sample surface differ due to change in the proportions of crystalline and amorphous volume fractions in the PGe layers. It was also shown that the implanted PGe layers before laser treatment were completely amorphous, but the action of intense radiation leads to local crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations